Hard coating film and image display device provided with same
By forming a hard coating layer with a specific composition on the polyimide substrate, the problem of insufficient hardness and bending resistance in the existing hard coating film in a flexible display device is solved, and a hard coating film with high hardness, scratch resistance and bending resistance is achieved.
Patent Information
- Application Number
- CN202380059519.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-23
- Filing Date
- 2023-09-15
- Publication Date
- 2025-03-11
AI Technical Summary
When used in flexible display devices, it is difficult to ensure sufficient hardness and bending resistance.
A polyimide substrate and a hard coating layer formed on the above-mentioned substrate are used, which consists of a light-transmissive resin, a photoinitiator and a solvent, and its elastic coefficient is determined to be in the range of 2,800 to 4,300 MPa by a nano-indenter.
The hard coat film has high hardness, excellent scratch resistance and significant bending resistance, and can be folded repeatedly at 3R (=3mm) for more than 200,000 times without breaking or cracks.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to a hard coating film and an image display device including the same, and more particularly, to a hard coating film having high hardness and excellent scratch resistance as well as excellent bending resistance, and an image display device including the hard coating film. Background Art
[0002] The hard coating film is used for surface protection of image display devices such as liquid crystal display devices, electroluminescent (EL) display devices, plasma display devices (PD), and field emission display devices (FED).
[0003] In recent years, flexible display devices or foldable display devices that can maintain display performance even when bent like paper by using flexible materials such as plastic or ultra-thin glass (UTG) instead of conventional inflexible glass substrates are rapidly emerging as the next generation of display devices. As a result, hard coatings with high hardness, good scratch resistance, and appropriate flexibility without cracking are also being studied.
[0004] Korean Patent Publication No. 10-2012-0078457 discloses a hard coating composition comprising an impact reinforcing agent having a rubber core and one or more shells, a photopolymerizable compound, and a photopolymerization initiator, and states that a hard coating film using the hard coating composition can achieve excellent scratch resistance, adhesion to the film, impact resistance, solvent resistance, processability, and bendability.
[0005] However, the hard coating film has a problem in that it is difficult to ensure hardness and bending resistance sufficient for application in flexible display devices. Summary of the invention
[0006] Technical issues
[0007] An object of the present invention is to provide a hard coating film having not only high hardness and excellent scratch resistance but also excellent bending resistance.
[0008] Another object of the present invention is to provide an image display device including the hard coat film.
[0009] Solution to the problem
[0010] In one aspect, the present invention provides a hard coating film comprising a polyimide substrate and a hard coating layer formed on the polyimide substrate.
[0011] When a load of 10 mN is applied, the elastic modulus (E IT) is 2,800 to 4,300 MPa.
[0012] In one embodiment of the present invention, the hard coat layer may be formed of a hard coat layer-forming composition including a light-transmitting resin, a photoinitiator, and a solvent. The light-transmitting resin may be of one or more types and satisfy the following Mathematical Formula 1.
[0013] [Mathematical formula 1]
[0014]
[0015] In the above formula,
[0016] X is the mixing ratio of a light-transmitting resin relative to the total amount of light-transmitting resin,
[0017] Mw is the weight average molecular weight of a light-transmitting resin.
[0018] n is the number of functional groups contained in one light-transmitting resin.
[0019] In one embodiment of the present invention, the light-transmitting resin may include one or more of a photocurable (meth)acrylate oligomer and a monomer.
[0020] In one embodiment of the present invention, the pencil hardness of the hard coating film may be 3H or higher.
[0021] In addition, the hard coating was coated with steel wool at 250 g / cm 2 After rubbing back and forth for more than 3,500 times with a load of 1000, no scratches are visible or less than 5 scratches are visible.
[0022] In one embodiment of the present invention, the hard coating film may not be broken or cracked after being repeatedly folded and unfolded 200,000 times or more at a radius of 3 mm so that the substrate surfaces are in contact with each other.
[0023] In another aspect, the present invention provides an image display device including the hard coat film.
[0024] In another aspect, the present invention provides a window of a flexible display device having the hard coating film.
[0025] In another aspect, the present invention provides a polarizing plate including the hard coat film.
[0026] In yet another aspect, the present invention provides a touch sensor including the hard coating film.
[0027] Effects of the Invention
[0028] The hard coating film of the present invention has not only high hardness and excellent scratch resistance, but also excellent bending resistance and can be folded repeatedly. Therefore, the hard coating film of the present invention can be effectively applied to flexible displays. DETAILED DESCRIPTION
[0029] Hereinafter, the present invention will be described in more detail.
[0030] One embodiment of the present invention relates to a hard coating film, which includes a polyimide substrate and a hard coating layer formed on the polyimide substrate. When a load of 10 mN is applied, the elastic modulus (E IT ) is 2,800 to 4,300 MPa.
[0031] The above elastic modulus (E IT ) is a value calculated from an indentation load-displacement curve obtained in a process where an indenter having a certain geometric shape is applied to the surface of the hard coating film at a load of 10 mN and then removed, and can be measured, for example, by the method described in the experimental examples described later.
[0032] The hard coating film according to one embodiment of the present invention has an elastic modulus (E) measured by a nanoindenter when a load of 10 mN is applied. IT ) is within the range of 2,800 to 4,300 MPa, which can improve hardness and scratch resistance, and significantly improve bending resistance. In particular, it is possible to achieve a pencil hardness of 3H or more and a bending resistance of more than 200,000 repeated outward folds at 3R (=3 mm).
[0033] In one embodiment of the present invention, the polyimide substrate refers to a substrate having a polyimide compound as a main component, for example, polyimide, polyamide-imide, etc., but it is not limited to these. As long as it is a substrate containing a polyimide compound used in the technical field, it can be used without particular limitation.
[0034] The thickness of the polyimide substrate is not particularly limited, and may be 8 to 1,000 μm, specifically 20 to 150 μm. If the thickness of the polyimide substrate is less than 8 μm, the strength of the film is reduced, resulting in poor processability. If the thickness is greater than 1,000 μm, there is a problem of reduced transparency or reduced bending resistance.
[0035] In one embodiment of the present invention, the hard coat layer is formed of a hard coat layer-forming composition including a light-transmitting resin, a photoinitiator, and a solvent. The light-transmitting resin may be of one or more types and satisfy the following Mathematical Formula 1.
[0036] [Mathematical formula 1]
[0037]
[0038] In the above formula,
[0039] X is the mixing ratio of a light-transmitting resin relative to the total amount of light-transmitting resin,
[0040] Mw is the weight average molecular weight of a light-transmitting resin.
[0041] n is the number of functional groups contained in one light-transmitting resin.
[0042] The above-mentioned mathematical formula 1 is a value calculated by adding the values obtained by dividing the weight average molecular weight (Mw) of each of the one or more light-transmitting resins contained in the hard coat layer forming composition by the number of functional groups (n) and multiplying by the weight ratio (X) of each light-transmitting resin relative to the total amount of the light-transmitting resin. By using a light-transmitting resin satisfying the above-mentioned mathematical formula 1, the elastic modulus (E) of the hard coat film can be increased. IT ) is adjusted to the above range, thereby achieving a hard coating film that has not only high hardness and excellent scratch resistance but also excellent bending resistance.
[0043] In one embodiment of the present invention, the light-transmitting resin may be a photocurable resin, and the photocurable resin may include a photocurable (meth)acrylate oligomer and / or monomer, but is not limited thereto.
[0044] As the photocurable (meth)acrylate oligomer, epoxy (meth)acrylate, urethane (meth)acrylate, polyhedral oligomeric silsesquioxane (meth)acrylate, etc. can be used, and urethane (meth)acrylate is preferred.
[0045] The above-mentioned urethane (meth) acrylate can be produced by reacting a (meth) acrylate having a hydroxyl group in the molecule with a compound having an isocyanate group in the presence of a catalyst. In terms of light resistance stability and mechanical properties, the above-mentioned urethane (meth) acrylate is preferably a trifunctional or higher aliphatic urethane (meth) acrylate. As specific examples of the above-mentioned trifunctional or higher aliphatic urethane (meth) acrylate, there are Miramer PU664, Miramer MU 9800 (above, Meiyuan Company), etc., but it is not limited thereto.
[0046] Specific examples of the (meth)acrylate having a hydroxyl group in the above-mentioned molecule include 2-hydroxyethyl (meth)acrylate, 2-hydroxyisopropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, caprolactone ring-opening hydroxy acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, etc. Specific examples of the above-mentioned compound having an isocyanate group include 1,4-diisocyanatobutane, 1,6-diisocyanatohexane, 1,8-diisocyanatooctane, 1,12-diisocyanatododecane, 1,5-diisocyanato-2-methylpentane, trimethyl-1,6-diisocyanatohexane, 1,3-bis(isocyanatomethyl)cyclohexane, trans-1,4-cyclohexene diisocyanate, 4,4'-methylenebis(cyclohexyl isocyanate), isocyanate, and the like. Phorone diisocyanate, toluene-2,4-diisocyanate, toluene-2,6-diisocyanate, xylene-1,4-diisocyanate, tetramethylxylene-1,3-diisocyanate, 1-chloromethyl-2,4-diisocyanate, 4,4'-methylenebis(2,6-dimethylphenylisocyanate), 4,4'-oxybis(phenylisocyanate), trifunctional isocyanates derived from hexamethylene diisocyanate, trimethylolpropane addition toluene diisocyanate, and the like.
[0047] The above-mentioned monomers may be any commonly used monomers without limitation, and are preferably monomers having an unsaturated group such as a (meth)acryloyl group, a vinyl group, a styryl group, an allyl group, etc. as a photocurable functional group in the molecule, and among them, monomers having a (meth)acryloyl group are preferred.
[0048] Specific examples of the monomer having a (meth)acryloyl group include neopentyl glycol acrylate, 1,6-hexanediol di(meth)acrylate, propylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, trimethylolethane tri(meth)acrylate, 1,2,4-cyclohexane tetra(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, isooctyl(meth)acrylate, (meth)acrylate. Isodecyl (meth)acrylate, stearyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, phenoxyethyl (meth)acrylate, isobornyl (meth)acrylate, trimethylolpropane (EO) 3 tri(meth)acrylate, trimethylolpropane (EO) 6 tri(meth)acrylate, trimethylolpropane (EO) 9 tri(meth)acrylate, glycerol (EO) 3 tri(meth)acrylate, glycerol (EO) 6 tri(meth)acrylate, glycerol (EO) 9 tri(meth)acrylate, pentaerythritol (EO) 4 tetra(meth)acrylate, pentaerythritol (EO) 8 tetra(meth)acrylate, pentaerythritol (EO) 12 Tetra(meth)acrylate, dipentaerythritol (EO)6 hexa(meth)acrylate, dipentaerythritol (EO) 12 Hexa(meth)acrylate and dipentaerythritol (EO) 18 One or more selected from the group consisting of hexa(meth)acrylates.
[0049] The photocurable (meth)acrylate oligomers and monomers exemplified above may be used alone or in combination of two or more.
[0050] The content of the light-transmitting resin may be 1 to 80% by weight, preferably 5 to 50% by weight, relative to 100% by weight of the entire hard coat layer-forming composition. If the content of the light-transmitting resin is less than 1% by weight, the elastic modulus of the coating decreases and cracks may easily occur in the coating when bent. If the content is more than 80% by weight, the viscosity increases and the coating property decreases, and the surface leveling may be insufficient, causing problems in appearance characteristics.
[0051] In one embodiment of the present invention, the photoinitiator is added to induce photocuring of the hard coat layer forming composition, and may include, for example, a photoradical initiator capable of generating radicals by light irradiation.
[0052] Examples of the photoinitiator include a type 1 initiator that generates free radicals by decomposing molecules due to differences in chemical structure or molecular bond energy, and a type 2 initiator that induces hydrogen decyclization by coexistence with a tertiary amine.
[0053] For example, the above-mentioned type 1 initiator may include: 4-phenoxydichloroacetophenone, 4-tert-butyldichloroacetophenone, 4-tert-butyltrichloroacetophenone, diethoxyacetophenone, 2-hydroxy-2-methyl-1-phenylpropane-1-one, 1-(4-isopropylphenyl)-2-hydroxy-2-methylpropane-1-one, 1-(4-dodecylphenyl)-2-hydroxy-2-methylpropane-1-one, 4-(2-hydroxyethoxy)-phenyl (2-hydroxy-2-propyl) ketone, 1-hydroxycyclohexyl phenyl ketone and other acetophenones; benzoin, benzoin methyl ether, benzoin ethyl ether, benzyl dimethyl ketal and other benzoin; phosphine oxides, titanocene compounds, etc.
[0054] For example, the type 2 initiator includes benzophenones such as benzoylbenzoic acid, benzoylbenzoic acid methyl ether, 4-phenylbenzophenone, hydroxybenzophenone, 4-benzoyl-4'-methyldiphenyl sulfide, and 3,3'-methyl-4-methoxybenzophenone; and thioxanthones such as thioxanthone, 2-chlorothioxanthone, 2-methylthioxanthone, 2,4-dimethylthioxanthone, and isopropylthioxanthone.
[0055] The above-mentioned photoinitiators may be used alone or in combination of two or more. In addition, the above-mentioned type 1 and type 2 initiators may be used alone or in combination.
[0056] The content of the photoinitiator may be about 0.1 to 10% by weight, preferably about 1 to 5% by weight, relative to 100% by weight of the entire hard coat-forming composition. When the content of the photoinitiator is less than 0.1% by weight, the curing speed of the composition may be slow, and sufficient curing may not be performed to ensure the mechanical properties and adhesion of the hard coat film or hard coat. When the content of the photoinitiator is higher than 10% by weight, poor adhesion, cracks, and curling may occur due to over-curing.
[0057] In one embodiment of the present invention, the solvent is a substance capable of dissolving or dispersing the above-mentioned components, and any solvent known in the art can be used without limitation.
[0058] As the solvent that can be used, preferably alcohols (methanol, ethanol, isopropanol, butanol, methyl cellosolve, ethyl cellosolve, etc.), ketones (methyl ethyl ketone, methyl butyl ketone, methyl isobutyl ketone, diethyl ketone, dipropyl ketone, cyclohexanone, etc.), acetates (ethyl acetate, propyl acetate, n-butyl acetate, tert-butyl acetate, methyl cellosolve acetate, ethyl cellosolve acetate, propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, propylene glycol monopropyl ether acetate, methoxybutyl acetate, methoxypentyl acetate, etc.), hexanes (hexane, heptane, octane, etc.), benzenes (benzene, toluene, xylene, etc.), ethers (diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol dipropyl ether, diethylene glycol dibutyl ether, propylene glycol monomethyl ether, etc.), etc. can be used. Each of the above-exemplified solvents can be used alone or in combination of two or more.
[0059] The content of the above-mentioned solvent may be 10 to 95% by weight, preferably 15 to 85% by weight, relative to 100% by weight of the entire hard coat layer forming composition. If the content of the above-mentioned solvent is lower than the above-mentioned range, the viscosity is high and the workability is poor. In addition, the swelling of the substrate may not be fully performed. On the contrary, if the content is higher than the above-mentioned range, there is a problem that the drying process takes a long time and the economic efficiency is poor. Therefore, it is appropriately used within the above-mentioned range.
[0060] In addition to the above components, the hard coating composition may further include components generally used in the art, such as additives such as a leveling agent, a UV stabilizer, a heat stabilizer, an antioxidant, a surfactant, a lubricant, and an antifouling agent.
[0061] The leveling agent is a component that imparts smoothness and coating properties to the coating film, and examples thereof include silicone leveling agents, fluorine leveling agents, and acrylic polymer leveling agents. These can be used alone or in combination of two or more.
[0062] The content of the leveling agent may be 0.1 to 1 wt % based on the total weight of the hard coating layer forming composition, but is not limited thereto.
[0063] The above-mentioned UV stabilizer is a component that prevents the cured hard coating from decomposing, changing color, or breaking due to exposure to ultraviolet rays by blocking or absorbing ultraviolet rays. The UV stabilizer can be: absorbers, quenchers, hindered amine light stabilizers (HALS, Hindered Amine Light Stabilizer), etc., which are classified according to the mechanism of action; or phenyl salicylate (Phenyl Salicylates, absorber), benzophenone (Benzophenone, absorber), benzotriazole (Benzotriazole, absorber), nickel derivatives (quenchers), etc., which are classified according to the chemical structure. They can be used alone or in combination of two or more.
[0064] Examples of the heat stabilizer include polyphenol-based heat stabilizers as primary heat stabilizers, phosphate-based heat stabilizers, and lactone-based heat stabilizers as secondary heat stabilizers. These heat stabilizers may be used alone or in combination of two or more.
[0065] The hard coat layer can be formed by applying the hard coat layer-forming composition on one or both surfaces of a polyimide substrate, drying the composition, and then subjecting the coating to UV curing.
[0066] The hard coat layer-forming composition can be applied to the substrate by a known method (coating process) such as a die coater, air knife, reverse roll, spray coating, doctor blade, casting, gravure, micro gravure, or spin coating.
[0067] After applying the hard coating layer-forming composition to a substrate, the volatile matter is evaporated at a temperature of 30 to 150°C for 10 seconds to 1 hour, more specifically 30 seconds to 30 minutes to dry, and then irradiated with UV light to cure. The irradiation amount of the UV light may be specifically about 0.01 to 10 J / cm 2 , more specifically 0.1 to 2 J / cm 2 .
[0068] At this time, the thickness of the formed hard coating layer may be specifically 2 to 30 μm, and more specifically 3 to 20 μm. When the thickness of the hard coating layer is within the above range, excellent hardness and bending resistance may be obtained.
[0069] One embodiment of the present invention relates to an image display device having the above-mentioned hard coating film. As an example, the hard coating film of the present invention can be used as a window of an image display device, particularly a flexible display device or a foldable display device. In addition, the hard coating film of the present invention can also be attached to a polarizing plate, a touch sensor, etc. for use.
[0070] The hard coating film of one embodiment of the present invention can be used for a reflective type, a transmissive type, a semi-transmissive type LCD or an LCD of various driving modes such as a TN type, a STN type, an OCB type, a HAN type, a VA type, an IPS type, etc. In addition, the hard coating film of one embodiment of the present invention can also be used for various image display devices such as a plasma display, a field emission display, an organic EL display, an inorganic EL display, and an electronic paper.
[0071] The present invention is described in more detail below by way of examples, comparative examples and experimental examples. These examples, comparative examples and experimental examples are only used to illustrate the present invention, and it is obvious to those skilled in the art that the scope of the present invention is not limited thereto.
[0072] Production Example 1: Production of a hard coat layer-forming composition
[0073] 28.4 parts by weight of tetrafunctional EO acrylate (MIRAMER M4004, Miura Chemical), 18.4 parts by weight of trifunctional acrylate (MIRAMER M300, Miura Chemical), 3 parts by weight of photoinitiator (Irgacure-184, Ciba Special Chemical), 1 part by weight of leveling agent (KY-1203, Shin-Etsu Chemical), and 49.2 parts by weight of methyl ethyl ketone were mixed with a stirrer and filtered with a filter made of PP to prepare a hard coat layer-forming composition.
[0074] Production Example 2: Production of a hard coat layer-forming composition
[0075] 28.4 parts by weight of tetrafunctional EO acrylate (MIRAMER M4004, Miura Chemicals), 18.4 parts by weight of hexafunctional acrylate (MIRAMER PU664, Miura Chemicals), 3 parts by weight of photoinitiator (Irgacure-184, Ciba Specialty Chemicals), 1 part by weight of leveling agent (DAC-HP, Daikin Chemicals), and 49.2 parts by weight of methyl ethyl ketone were mixed with a stirrer and filtered with a filter made of PP to prepare a hard coat layer-forming composition.
[0076] Production Example 3: Production of a hard coat layer-forming composition
[0077] 23 parts by weight of hexafunctional acrylate (MIRAMER PU664, Miura Chemicals), 23.9 parts by weight of nonafunctional acrylate (MIRAMER MU9800, Miura Chemicals), 3 parts by weight of photoinitiator (Irgacure-184, Ciba Specialty Chemicals), 0.5 parts by weight of leveling agent (KY-1203, Shin-Etsu Chemicals), and 49.6 parts by weight of methyl ethyl ketone were mixed with a stirrer and filtered with a filter made of PP to prepare a hard coat layer-forming composition.
[0078] Production Example 4: Production of a hard coat layer-forming composition
[0079] 46.8 parts by weight of tetrafunctional EO acrylate (MIRAMER M4004, Miramer), 3 parts by weight of a photoinitiator (Irgacure-184, Ciba Specialty Chemicals), 1 part by weight of a leveling agent (KY-1203, Shin-Etsu), and 49.2 parts by weight of methyl ethyl ketone were mixed with a stirrer and filtered with a filter made of PP to prepare a hard coat layer-forming composition.
[0080] Production Example 5: Production of a hard coat layer-forming composition
[0081] 9.4 parts by weight of tetrafunctional EO acrylate (MIRAMER M4004, Miura Chemicals), 37.4 parts by weight of trifunctional acrylate (MIRAMER M300, Miura Chemicals), 3 parts by weight of photoinitiator (Irgacure-184, Ciba Specialty Chemicals), 1 part by weight of leveling agent (DAC-HP, Daikin Chemicals), and 49.2 parts by weight of methyl ethyl ketone were mixed with a stirrer and filtered with a filter made of PP to prepare a hard coat layer-forming composition.
[0082] Production Example 6: Production of a hard coat layer-forming composition
[0083] 30.4 parts by weight of hexafunctional acrylate (MIRAMER PU664, Miura Chemicals), 16.4 parts by weight of difunctional acrylate (MIRAMER SC2404, Miura Chemicals), 3 parts by weight of photoinitiator (Irgacure-184, Ciba Specialty Chemicals), 1 part by weight of leveling agent (KY-1203, Shin-Etsu Corporation), and 49.2 parts by weight of methyl ethyl ketone were mixed with a stirrer and filtered with a filter made of PP to prepare a composition for forming a hard coat layer.
[0084] Production Example 7: Production of a hard coat layer-forming composition
[0085] 46.7 parts by weight of trifunctional acrylate (MIRAMER M300, Miramer), 3 parts by weight of photoinitiator (Irgacure-184, Ciba Specialty Chemicals), 0.3 parts by weight of leveling agent (BYK-307), and 50 parts by weight of methyl ethyl ketone were mixed with a stirrer and filtered with a filter made of PP to prepare a hard coat layer-forming composition.
[0086] Production Example 8: Production of a hard coat layer-forming composition
[0087] 46.9 parts by weight of a difunctional acrylate (MIRAMER SC2404, Miramer), 3 parts by weight of a photoinitiator (Irgacure-184, Ciba Specialty Chemicals), 0.5 parts by weight of a leveling agent (KY-1203, Shin-Etsu), and 49.6 parts by weight of methyl ethyl ketone were mixed with a stirrer and filtered with a filter made of PP to prepare a hard coat layer-forming composition.
[0088] Production Example 9: Production of a hard coat layer-forming composition
[0089] 23.9 parts by weight of tetrafunctional EO acrylate (MIRAMER M4004, Miura Chemicals), 23 parts by weight of difunctional acrylate (MIRAMER SC2404, Miura Chemicals), 3 parts by weight of photoinitiator (Irgacure-184, Ciba Specialty Chemicals), 0.5 parts by weight of leveling agent (KY-1203, Shin-Etsu Chemicals), and 49.6 parts by weight of methyl ethyl ketone were mixed with a stirrer and filtered with a filter made of PP to prepare a hard coat layer-forming composition.
[0090] Example 1: Preparation of hard coating film
[0091] The hard coat-forming composition of Production Example 1 was applied onto a polyimide substrate (Sumitomo Chemical Co., Ltd., 50 μm) in such a manner that the thickness after curing was 8 μm. After the solvent was dried, the substrate was irradiated with UV light at a cumulative dose of 600 mJ / cm in a nitrogen atmosphere. 2 , thereby producing a hard coating film.
[0092] Example 2: Preparation of hard coating film
[0093] The hard coat-forming composition of Production Example 2 was applied to a polyimide substrate (Sumitomo Chemical Co., Ltd., 50 Chemical Co., Ltd.) in such a manner that the thickness after curing was 8 μm. After the solvent was dried, the substrate was irradiated with UV light with a cumulative amount of 600 mJ / cm in a nitrogen atmosphere. 2 , thereby producing a hard coating film.
[0094] Example 3: Preparation of hard coating film
[0095] The hard coat-forming composition of the above-mentioned manufacturing example 3 was coated on a polyimide-based substrate (Sumitomo Chemical Co., Ltd., 50 Chemical Co., Ltd.) in such a manner that the thickness after curing was 8 % hard coat. After the solvent was dried, the substrate was irradiated with UV with a cumulative light intensity of 600 mJ / cm in a nitrogen atmosphere. 2 , thereby producing a hard coating film.
[0096] Example 4: Preparation of hard coating film
[0097] The hard coat-forming composition of the above-mentioned manufacturing example 4 was coated on a polyimide-based substrate (Sumitomo Chemical Co., Ltd., 50 Chemical Co., Ltd.) in such a manner that the thickness after curing was 8 % hard coat. After the solvent was dried, the substrate was irradiated with UV with a cumulative light intensity of 600 mJ / cm in a nitrogen atmosphere. 2 , thereby producing a hard coating film.
[0098] Example 5: Preparation of hard coating film
[0099] The hard coat-forming composition of the above-mentioned manufacturing example 5 was coated on a polyimide-based substrate (Sumitomo Chemical Co., Ltd., 50 Chemical Co., Ltd.) in such a manner that the thickness after curing was 8 % hard coat. After the solvent was dried, the substrate was irradiated with UV with a cumulative light intensity of 600 mJ / cm in a nitrogen atmosphere. 2 , thereby producing a hard coating film.
[0100] Example 6: Preparation of hard coating film
[0101] The hard coat-forming composition of the above-mentioned manufacturing example 6 was coated on a polyimide-based substrate (Sumitomo Chemical Co., Ltd., 50 Chemical Co., Ltd.) in such a manner that the thickness after curing was 8 % hard coat. After the solvent was dried, the substrate was irradiated with UV with a cumulative light intensity of 600 mJ / cm in a nitrogen atmosphere. 2 , thereby producing a hard coating film.
[0102] Comparative Example 1: Preparation of hard coating film
[0103] The hard coat-forming composition of the above-mentioned manufacturing example 7 was coated on a polyimide-based substrate (Sumitomo Chemical Co., Ltd., 50 Chemical Co., Ltd.) in such a manner that the thickness after curing was 8 % hard coat. After the solvent was dried, the substrate was irradiated with UV with a cumulative light intensity of 600 mJ / cm in a nitrogen atmosphere. 2 , thereby producing a hard coating film.
[0104] Comparative Example 2: Preparation of hard coating film
[0105] The hard coat-forming composition of the manufacturing example 8 was coated on a polyimide substrate (Sumitomo Chemical Co., Ltd., 50 Chemical Co., Ltd.) in such a manner that the thickness after curing was 8 hard coats. After the solvent was dried, the substrate was irradiated with UV with a cumulative light intensity of 600 mJ / cm in a nitrogen atmosphere. 2 , thereby producing a hard coating film.
[0106] Comparative Example 3: Preparation of hard coating film
[0107] The hard coat-forming composition of the above-mentioned manufacturing example 9 was coated on a polyimide-based substrate (Sumitomo Chemical Co., Ltd., 50 Chemical Co., Ltd.) in such a manner that the thickness after curing was 8 % hard coat. After the solvent was dried, the substrate was irradiated with UV with a cumulative light intensity of 600 mJ / cm in a nitrogen atmosphere. 2 , thereby producing a hard coating film.
[0108] Comparative Example 4: Preparation of hard coating film
[0109] The hard coat layer-forming composition of the above-mentioned manufacturing example 1 was applied on a polyethylene terephthalate film (PET, 50ET cloth) in such a manner that the thickness after curing was 8 Å, and after the solvent was dried, UV cumulative light of 600 mJ / cm was irradiated in a nitrogen atmosphere. 2 , thereby producing a hard coating film.
[0110] Experimental Example 1:
[0111] The physical properties of the films produced in the above-mentioned Examples and Comparative Examples were measured by the methods described below. The results are shown in Table 1 below.
[0112] (1) Elastic modulus (E IT ) determination
[0113] The elastic modulus (E IT ) was measured, and the results are shown in Table 1 below. Specifically, a nanoindenter (Fisher) was used to measure the elastic modulus (E) when a load of 10 mN was applied for 15 seconds using an indenter in the form of a triangular pyramid tip (Vickers tip) to the surface of the hard coating film or the surface of the substrate before the hard coating film was produced. IT ).
[0114] (2) Pencil hardness
[0115] The hard coating films produced in the above-mentioned manufacturing examples and comparative examples were fixed on glass, and the hard coating surface of the film was evaluated five times with pencils having various pencil hardnesses under a load of 750 g. The pencil hardness was expressed as the hardness that was not scratched four or more times.
[0116] (3) Scratch resistance
[0117] The hard coating films produced in the above-mentioned production examples and comparative examples were fixed with tape so that the coated surface faced upward, and then the hard coating films were rubbed with steel wool (#0000) at a pressure of 250 g / cm 2 The test piece was rubbed back and forth 3,500 times with a load of 10000, and then the scratches were observed by transmission and reflection of the measurement part under a three-wavelength lamp. The scratch resistance was evaluated according to the following evaluation criteria.
[0118] <Evaluation Criteria>
[0119] ○: No scratches or 5 or less scratches were observed;
[0120] ×: More than 5 scratches were seen.
[0121] (4) Bending resistance
[0122] The hard coating films prepared in the above manufacturing examples and comparative examples were folded and unfolded 200,000 times with the hard coating surface folded outward at a curvature radius of 3 mm to observe whether the film was broken and whether cracks in the hard coating layer were generated. The bending resistance was evaluated according to the following evaluation criteria.
[0123] <Evaluation Criteria>
[0124] ○: No film breakage or hard coating cracks
[0125] ×: Film breakage or hard coating cracks occur
[0126] (5) Contact angle measurement
[0127] After dropping a liquid on the hard coating film produced in the above-mentioned production examples and comparative examples, the water contact angle was measured using a contact angle meter DSA100 manufactured by KRUSS. The amount of the droplet was set to 2 water contacts at room temperature.
[0128] (6) Adhesion
[0129] For the hard coating films produced in the above manufacturing examples and comparative examples, the base film was bonded to the glass using a transparent adhesive with the coated surface facing upward, and 100 squares were cut horizontally and vertically at intervals of 1 mm on the coated surface using a cutter, and then the adhesion test was performed three times using a Mikibond tape. After rapid peeling at a peeling angle of 180 degrees, the degree of peeling of the coated surface was observed with the naked eye, and the adhesion was evaluated according to the following evaluation criteria.
[0130] <Evaluation Criteria>
[0131] 5B: The area left is 100%;
[0132] 4B: The area left is more than 95% and less than 100%;
[0133] 3B: The area left is more than 85% and less than 95%;
[0134] 2B: The area left is more than 65% and less than 85%;
[0135] 1B: The area left is more than 45% and less than 65%;
[0136] 0B: The area left is less than 45%.
[0137] [Table 1]
[0138]
[0139] As shown in Table 1, it can be confirmed that the elastic coefficient (E IT The hard coating films of Examples 1 to 6 with a hardness of 2,800 to 4,300 MPa showed a pencil hardness of 3H or more and excellent scratch resistance, and showed bending resistance of more than 200,000 repeated outward folds at 3R (=3 mm).
[0140] On the other hand, the elastic modulus (E IT ) The hard coating films of Comparative Examples 1 to 3 deviating from the range of 2,800 to 4,300 MPa showed a result that pencil hardness, scratch resistance, and bending resistance could not be simultaneously ensured.
[0141] In addition, it was confirmed that the hard coating film of Comparative Example 4 using a polyethylene terephthalate film as a substrate was inferior in pencil hardness and adhesion.
[0142] The above describes specific parts of the present invention. It is obvious to those skilled in the art that these specific descriptions are only preferred embodiments, and the scope of the present invention is not limited thereto. Those skilled in the art should be able to make various applications and modifications within the scope of the present invention based on the above contents.
[0143] Therefore, the actual scope of the present invention should be determined by the appended claims and their equivalents.
Claims
1. A hard coating film comprising a polyimide substrate and a hard coating layer formed on the polyimide substrate, When a load of 10 mN is applied, the elastic modulus E is measured by a nanoindenter. IT 2,800 to 4,300MPa.
2. The hard coating film according to claim 1, wherein the hard coating layer is formed of a hard coating layer-forming composition comprising a light-transmitting resin, a photoinitiator, and a solvent, wherein the light-transmitting resin is one or more and satisfies the following Mathematical Formula 1: [Mathematical formula 1] In the formula, X is the mixing ratio of a light-transmitting resin relative to the total amount of light-transmitting resin, Mw is the weight average molecular weight of a light-transmitting resin. n is the number of functional groups contained in one light-transmitting resin. 3 . The hard coating film according to claim 2 , wherein the light-transmitting resin comprises one or more of a photocurable (meth)acrylate oligomer and a monomer. The hard coating film according to claim 1 , which has a pencil hardness of 3H or more.
5. The hard coating film according to claim 1, wherein the hard coating layer is formed by using steel wool at a pressure of 250 g / cm 2 After rubbing back and forth for more than 3,500 times with a load of 1000, no scratches are visible or 5 or less scratches are visible.
6. The hard coating film according to claim 1, which does not break or crack after being repeatedly folded and unfolded 200,000 times or more at a radius of 3 mm in such a manner that the substrate surfaces are in contact with each other. 7 . An image display device comprising the hard coating film according to claim 1 . 8 . A window of a flexible display device, comprising the hard coating film according to claim 1 . 9 . A polarizing plate comprising the hard coating film according to claim 1 . 10 . A touch sensor comprising the hard coating film according to claim 1 .
Citation Information
Patent Citations
Hard coating composition and laminate comprising hard coating layer
KR1020120078457A